Physico-chemical Properties of Nutmeg (Myristica fragrans houtt) of North Sulawesi Nutmeg - Dino Rahardiyan; Mario Poluakan; Emma Mauren Moko (Jurnal Kimia Fullerene, 2020)
Essential oil of nutmeg (Myristica fragrans houtt) is one of the many potentials of nutmeg that has a high economic value although in North Sulawesi it has not been exploited to its full potential. This research was conducted to compare the yield and properties of Nutmeg oil extract from the seeds and mace of Talaud and North Minahasa-North Sulawesi. The oil extract was obtained by distillation and was further characterized in terms of color, solubility in ethanol, density, optical rotation, refractive index. Results of this research exhibited that oil of the mace of nutmeg from Talaud had a lighter appearance in color compared to that from North Minahasa, while the density of oil extracted from North Minahasa was more densed compared to Talaud in both seed and mace (0.923 and 0.938 respectively at 25°C). The reflective index of nutmeg oil from North Minahasa was slightly higher than of Talaud both from seed and mace (1.4834 and 1.493 at 25°C), while the optical rotations of oil extracted from the mace were between +6.90° to +9.80° and from the seed were +20.73° to +22.30°.